Chondrosarcoma of Posterior Nasal Septum - Gurung, U; Joy, L; Thapa, NM; Pradhan, B (Kathmandu University Medical Journal, 2013)
Chondrosarcoma is a rare non-epithelial tumor comprising of 10-20% of primary bone tumor. The nasal septum is a rare site for its occurrence. We present one such case of chondrosarcoma of the nasal septum who was treated with endoscopic removal followed by post operative radiotherapy and discuss the relevant clinical presentation, diagnosis and treatment and review the literature also. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 89-91 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7352